2022
DOI: 10.1007/s12602-022-09922-8
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis WF2R11 Suppresses PM2.5-Mediated Activation of the Aryl Hydrocarbon Receptor in HaCaT Keratinocytes

Abstract: The skin supports a diverse microbiome whose imbalance is related to skin inflammation and diseases. Exposure to fine particulate matter (PM2.5), a major air pollutant, can adversely affect the skin microbiota equilibrium. In this study, the effect and mechanism of PM2.5 exposure in HaCaT keratinocytes were investigated. PM2.5 stimulated the aryl hydrocarbon receptor (AhR) to produce reactive oxygen species (ROS) in HaCaT cells, leading to mitochondrial dysfunction and intrinsic mitochondrial apoptosis. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…This air pollutant was able to stimulate AhR to produce ROS and inflammatory cytokines, eliciting apoptosis. These authors found out that the supernatant derived specifically from the S. epidermidis WF2R11 was able to revert these PM2.5-induced effects by inhibiting AhR activation [ 149 ].…”
Section: Microbiota and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This air pollutant was able to stimulate AhR to produce ROS and inflammatory cytokines, eliciting apoptosis. These authors found out that the supernatant derived specifically from the S. epidermidis WF2R11 was able to revert these PM2.5-induced effects by inhibiting AhR activation [ 149 ].…”
Section: Microbiota and Oxidative Stressmentioning
confidence: 99%
“…For example, the administration of L. casei YIT9018 or L. reuteri , two well-known probiotics with anti-inflammatory and antioxidant properties, reduced the incidence of melanoma, metastatic lesion, and significantly prolonged survival in B16 melanoma-bearing animals [ 177 , 178 ]. A diminished content of the skin commensal C. acnes and its secreted product RoxP, with antioxidant properties, has been found in BCC tissues [ 149 ]. Moreover, intra-tumoral injection of C. acnes in a melanoma mouse model significantly decreased melanoma growth and size [ 66 ].…”
Section: The Interplay Between Microbiota Oxidative Stress and Skin C...mentioning
confidence: 99%